Conceptualizing music : cognitive structure, theory, and analysis - Zbikowski, Lawrence Michael; Oxford University Press (Oxford ; New York : Oxford University Press, 2002)
"Music theory is often seen as an arcane and somewhat forbidding discipline which stands at a distance from the sweet pleasure and sensuous thrill that is music. Theory, according to this view, is concerned with scales and chords and intervals, or with complicated and highly abstract systems of musical relationships. It is not concerned with how music captivates us. But Lawrence Zbikowski argues that this common view of music theory is wrong. Theorizing about music is something we do every time we try to make sense of our musical experience, and it involves the same cognitive capacities we use to make sense of the world as a whole.
The play of concepts and conceptual structures typical of music theory is thus not something remote from our appreciation of music, but is instead basic to it."--BOOK JACKET.
Introduction: Conceptualizing Music -- 1. Categorization -- 2. Cross-Domain Mapping -- 3. Conceptual Models and Theories -- 4. Categorization, Compositional Strategy, and Musical Syntax -- 5. Cultural Knowledge and Musical Ontology -- 6. Words, Music, and Song: The Nineteenth-Century Lied -- 7. Competing Models of Music: Theories of Musical Form and Hierarchy -- Conclusion: Cognitive Structure, Theory, and Analysis.
Includes bibliographical references (pages 335-352) and index.
Keywords: Musical perception; Musical analysis; Cognition